NOGAPS-ALPHA model simulations of stratospheric ozone during the SOLVE2 campaign - Mccormack, J. P.; Eckermann, S. D.; Coy, L.; Allen, D. R.; Kim, Y.-J.; Hogan, T.; Lawrence, B.; Stephens, A.; Browell, E. V.; Burris, J.; Mcgee, T.; Trepte, C. R. (HAL CCSD, 2004)
International audience This paper presents three-dimensional prognostic O 3 simulations with parameterized gas-phase photochemistry from the new NOGAPS-ALPHA middle atmosphere forecast model. We compare 5-day NOGAPS-ALPHA hindcasts of stratospheric O 3 with satellite and DC-8 aircraft measurements for two cases during the SOLVE II campaign: (1) the cold, isolated vortex during 11-16 January 2003; and (2) the rapidly developing stratospheric warming of 17-22 January 2003. In the first case we test three different photochemistry parameterizations. NOGAPS-ALPHA O 3 simulations using the NRL-CHEM2D parameterization give the best agreement with SAGE III and POAM III profile measurements. 5-day NOGAPS-ALPHA hindcasts of polar O 3 initialized with the NASA GEOS4 analyses produce better agreement with observations than do the operational ECMWF O 3 forecasts of case 1. For case 2, both NOGAPS-ALPHA and ECMWF 114-h forecasts of the split vortex structure in lower stratospheric O 3 on 21 January 2003 show comparable skill. Updated ECMWF O 3 forecasts of this event at hour 42 display marked improvement from the 114-h forecast; corresponding updated 42-hour NOGAPS-ALPHA prognostic O 3 fields initialized with the GEOS4 analyses do not improve significantly. When NOGAPS-ALPHA prognostic O 3 is initialized with the higher resolution ECMWF O 3 analyses, the NOGAPS-ALPHA 42-hour lower stratospheric O 3 fields closely match the operational 42-hour ECMWF O 3 forecast of the 21 January event. We find that stratospheric O 3 forecasts at high latitudes in winter can depend on both model initial conditions and the treatment of photochemistry over periods of 1-5 days. Overall, these results show that the new O 3 initialization, photochemistry parameterization, and spectral transport in the NOGAPS-ALPHA NWP model can provide reliable short-range stratospheric O 3 forecasts during Arctic winter.